Investigation of traffic‐induced vibration in Vilnius Arch‐Cathedral Belfry - Kliukas, Romualdas; Jaras, Arūnas; Kačianauskas, Rimantas (Transport, 2008)
The influence of city traffic‐induced vibration on Vilnius Arch‐Cathedral Belfry is investigated. Two sources of dynamic excitation are studied. Conventional city traffic is considered to be a natural source of excitation while excitation imposed artificially by moving a heavily loaded truck is considered to be the source of increased risk excitation. The influence of induced vibrations is recorded by accelerometers located in various positions of the Belfry’s structures and shown by accelerograms. Dynamic effects are evaluated by considering acceleration magnitudes and response spectra. A comparative analysis of both effects is presented and conclusions and recommendations are provided. First published online: 27 Oct 2010